Impact of Attitudes and Social Norms on AQUA Purchase Decisions: The Role of Buying Intent in Jabodetabek - Afrina, Fitri; Saputra, Fendi (IJBLE Scientific Publications Community Inc., 2024)
This study examines the influence of attitudes and subjective norms on purchasing decisions for AQUA mineral water, with purchase intention as a mediating variable. Using a quantitative approach, data were collected through questionnaires from 220 Aqua consumers in Greater Jakarta, selected via purposive sampling. Data analysis was conducted with SmartPLS 4.1 using Partial Least Square (PLS), assessing both outer and inner models. Findings reveal that attitudes and subjective norms significantly impact purchasing decisions. However, purchase intention does not affect purchasing decisions and does not mediate the relationship between attitudes, subjective norms, and purchasing decisions.